PENGARUH PENGENDALIAN DIRI DAN STRES KERJA TERHADAP PERILAKU CYBERLOAFING PADA DOSEN DI INDONESIA - Kartinah, Kartinah; Saifulah, Anang Maruf; Anisah, Tiara Nur; Nurwiyanta, Nurwiyanta; Sunyoto, Danang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to examine the influence of personality, the influence of self-control and work stress on cyberloafing behavior. The population in this study are lecturers in Indonesia. Sampling in this study used a non-probability sampling (convenience sampling) technique. Determination tests, F statistical tests and t statistical tests are carried out to answer the research hypothesis. The results of this study show that self-control negatively affects cyberloafing behavior and work stress has a positive effect on cyberloafing behavior. The study has a regression model = -5.064 - 0.206 X1 + 0.755 X2 with an R Square value of 0.357.